ANALISIS KELENGKAPAN PENGISIAN DATA FORMULIR ANAMNESIS DAN PEMERIKSAAN FISIK KASUS BEDAH - Rd. Irda Melinda Febriyanti; Ida Sugiarti (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
AbstractQuantitative analysis has conducted in dr. Slamet Garut General Hospital, but there are still anamnesis andphysical examination forms are incomplete both clinical data and demographic data. Based on the highestpreliminary survey of incompleteness on the register component is 83.34%. The aim of this research is toknow the fulfilment procedure, completeness and incompleteness data fulfilment of anamnesis and physicalexamination forms. The method that used in this research is observation quantitative analysis, using instrumentobservation sheet. The population in this research are 1008 medical record documents on semester I in 2013.The magnitude of the sample uses Slovin formula is 90 documents. Slovin formula is used because it refersto large samples which are 90 documents. The result of research showed that complete form anamnesis andphysical examination of the patient identification component is 20%, important report is 31.12%, authenticationis 83.33% dan the register is 3.34%. Refers to the minimum standard of completeness which is submitted bythe department of health (2006), the completeness document must be 100%. It can be conclusion that theanamnesis and physical examination data fulfilment in dr. Slamet Garut General Hospital is not complete.Preferably, socialization is needed in fulfilment medical record document which is adapted to the StandardOperational Procedure (SOP) or The Fixed Procedure (PROTAP) which is adapted to all units related personalhealth such as doctors, nurses, dan medical record officer.Key words : Completeness, Filling up data, Anamnesis and physical examination.AbstrakDi RSUD dr. Slamet Garut sudah dilakukan analisis kuantitatif tetapi masih terdapat formulir anamnesisdan pemeriksaan fisik yang kurang lengkap baik data demografi maupun data klinis. Berdasarkan surveypendahuluan ketidaklengkapan yang tertinggi pada komponen pencatatan 83,34%. Tujuan penelitian ini untukmengetahui prosedur pengisian, kelengkapan dan ketidaklengkapan pengisian data formulir anamnesis danpemeriksaan fisik. Penelitian ini menggunakan metode analisis kuantitatif yaitu observasi, dengan menggunakaninstrumen lembar observasi. Populasi dalam penelitian ini sebanyak 1008 dokumen rekam medis padasemester I tahun 2013. Besarnya sampel menggunakan rumus Slovin sebanyak 90 dokumen. Hasil penelitianmenunjukan kelengkapan formulir anamnesis dan pemeriksaan fisik komponen identifikasi pasien sebanyak20%, laporan penting 31,12%, authentikasi 83,33% dan pencatatan 3,34% . Mengacu pada standar minimalkelengkapan dokumen yang diajukan departemen kesehatan (2006) kelengkapan dokumen harus 100%.Maka dapat disimpulkan pengisian data formulir anamnesis dan pemeriksaan fisik di RSUD dr. Slamet Garuttidak lengkap. Sebaiknya, diadakan sosialisasi dalam pengisian dokumen rekam medis disesuaikan denganStandar Operasional Prosedur (SOP) atau Prosedur Tetap (PROTAP) yang telah ditetapakan pada semua unitpelayanan kepada tenaga kesehatan terkait seperti : dokter, perawat dan petugas rekam medis.Kata Kunci: Kelengkapan, Pengisian data, Anamnesis dan Pemeriksaan Fisik